2016
DOI: 10.3989/revmetalm.070
|View full text |Cite
|
Sign up to set email alerts
|

Statistical study to determine the effect of carbon, silicon, nickel and other alloying elements on the mechanical properties of as-cast ferritic ductile irons

Abstract: ABSTRACT:There is a great interest in fully ferritic ductile irons due to their structural homogeneity, remarkable ductility and good response when machining. On the other hand the wide variety of raw materials available in foundry plants becomes a problem when controlling the chemical composition of the manufactured alloys. The present work shows a statistical study about the effect of different C, Si, Ni contents and other minor elements on structural and mechanical properties of a group of ferritic ductile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Their classification depends on its metallographic structure, according to the percentages of carbon and other alloying elements. Although these materials do not have the mechanical properties of steels, they are used in numerous applications such as: hydraulic valves, transmissions, gears, nuts, shafts, hydraulic components, pistons, guides or engine liners [1].…”
Section: Introductionmentioning
confidence: 99%
“…Their classification depends on its metallographic structure, according to the percentages of carbon and other alloying elements. Although these materials do not have the mechanical properties of steels, they are used in numerous applications such as: hydraulic valves, transmissions, gears, nuts, shafts, hydraulic components, pistons, guides or engine liners [1].…”
Section: Introductionmentioning
confidence: 99%
“…These mechanical properties are a result of the microstructure of the material (Pan et al, 2012). For this reason, the requirements of these manufacturers include a volume fraction of pearlite lower than 5%, in addition to a spheroidal morphology in the primary graphite (Lacaze et al, 2016). Recent studies have shown that factors such as graphite morphology and the number of graphite nodules per unit area have a significant effect on the in-service behaviour of the material, especially its fatigue strength (Shiraki et al, 2016).…”
Section: Introductionmentioning
confidence: 99%